2012
DOI: 10.1155/2012/867415
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes and Thyroid Autoimmunity

Abstract: Background. About 10% of pregnancies are complicated by previously unknown impairment of glucose metabolism, which is defined as gestational diabetes. There are little data available on prevalence of thyroid disorders in patients affected by gestational diabetes, and about their postgestational thyroid function and autoimmunity. We therefore investigated pancreatic and thyroid autoimmunity in gestational diabetic patients and in women who had had a previous gestational diabetic pregnancy. Methods. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…In current study, women with gestational diabetes had normal TSH, but 10 % of them had free T 4 level below normal range. But in a study of Vitacolonna et al 15 there was no significant association between gestational diabetes and free T 4 level. Our data confirm the result of previous studies showing free T 4 level in women with diabetes mellitus type I significantly lower than healthy pregnant women.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In current study, women with gestational diabetes had normal TSH, but 10 % of them had free T 4 level below normal range. But in a study of Vitacolonna et al 15 there was no significant association between gestational diabetes and free T 4 level. Our data confirm the result of previous studies showing free T 4 level in women with diabetes mellitus type I significantly lower than healthy pregnant women.…”
Section: Discussionmentioning
confidence: 85%
“…In another study done by Vitacolonna and et al 15 reported, in case group, the average maternal age and BMI of 33 years old and 29.8 kg/cm 2 respectively, and the average maternal age and BMI of 29 years old and 28.1 kg/cm 2 respectively in control group.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, thyroid disorders, the most common endocrine disorders in women of childbearing age [2], are more prevalent in pregnant women with GDM, compared to their healthy counterparts [5]. Also, a signi cant increase in incident thyroid autoimmunity has been reported among women with a history of GDM (31.6% vs. 9.7%) [1]. It has also been shown that clinical and subclinical hypothyroidism is more common among women with T2DM, compared to non-diabetic women [6,7], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found a higher prevalence of thyroid autoimmunity in GDM compared to healthy controls; therefore they suggest that it would be appropriate to extend screening for thyroid diseases to women with GDM [10]. Higher prevalence of thyroid autoimmunity has been found in women who have had previous GDM and has been speculated that gestational hyperglycemia may trigger thyroid autoimmunity [11]. Some sudies have shown that instead of the presence of TPOAb, overt hypothyroidism causes an increase in the formation of diabetes mellitus [12].…”
Section: Introductionmentioning
confidence: 99%